Recent Advancements in Sustainable Solar Photovoltaic Power Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Energy plays a decisive role in realizing the Sustainable Development Goals (SDGs), such as employment growth, industry, innovation, and infrastructure, sustainable cities and communities, clean energy, and climate change. This reprint, titled “Recent Advancements in Sustainable Solar Photovoltaic Power Technology”, presents significant works in the field of solar photovoltaic systems and critical issues in solar power generation technology, as well as the latest achievements and current problems in solar power generation technology and proposing corresponding solutions to key technical challenges in the utilization of solar power, pointing out future directions for achieving the SDGs through solar power generation technology.This reprint provides a variety of comprehensive reviews on solar power generation technologies like maximum power point tracking (MPPT) techniques, power electronic converter topologies, and parameter estimation of PV cells. Along with reviews, this book also outlines the latest developments in the field of MPPTs, converters, cooling systems, rooftop, as well as grid-connected PV systems. This reprint will serve as a reference and update for academics, researchers, and practicing engineers to inspire new research and developments that pave the way for next-generation PV systems for residential and small commercial applications.This reprint includes three reviews and twelve articles focused on solar photovoltaic power technology.